Development and deployment of a functional 3D-bioprinted blood vessel - Annika C. Dell; Jamie Maresca; Bruce A. Davis; Toshihiko Isaji; Alan Dardik; John P. Geibel (Scientific Reports)
Abstract Creating vascular structures in vitro via bioprinting to replace damaged or missing vasculature has significant advantages over current surgical methods of vessel replacement. Using rat fibroblasts and smooth muscle cells, we have bioprinted a rat aorta using a rotating mandrel method to create the tubular replacement structure. Then, the 3D-bioprinted aortas were implanted into rats to determine their functionality long-term in vivo. The implanted vascular conduits were well-tolerated, well-incorporated into native vasculature, and showed the physiological behavior of a native vessel. The development and deployment of 3D-bioprinted vessels for repair of large vessels in an animal model paves the way for advancements in the treatment of vascular disease in humans.